Aging associated changes in the motor control of ankle movements in the brain - Linortner, P; Jehna, M; Johansen-Berg, H; Matthews, P; Schmidt, R; Fazekas, F; Enzinger, C (Elsevier, 2014)
Although age-related gait changes have been well characterized, little is known regarding potential functional changes in central motor control of distal lower limb movements with age. We hypothesized that there are age-related changes in brain activity associated with the control of repetitive ankle movements, an element of gait feasible for study with functional magnetic resonance imaging. We analyzed standardized functional magnetic resonance imaging data from 102 right-foot dominant healthy participants aged 20-83years for age-associated effects using FSL and a meta-analysis using coordinate-based activation likelihood estimation. For the first time, we have confirmed age-related changes in brain activity with this gait-related movement of the lower limb in a large population. Increasing age correlated strongly with increased movement-associated activity in the cerebellum and precuneus. Given that task performance did not vary with age, we interpret these changes as potentially compensatory for other age-related changes in the sensorimotor network responsible for control of limb function. © 2014 Elsevier Inc.